Information Literacy Ability of Library Students of UIN Sumatra Utara in Thesis Preparation Using The Empowering Eight Model - Tilawah, Indri Sukma (International Journal of Cultural and Social Science, 2023)
This study discusses the information literacy skills of Library Science students at UIN Sumatera Utara in preparing their thesis using the empowering eight models. This study aims to determine the level of information literacy skills of Library Science students in the preparation of their thesis. This type of research is a quantitative study with a descriptive approach. The population in the study were all library science students at UIN Sumatra Utara 2016, a total of 58 people. While the sample in this study was determined based on several criteria (using purposive sampling) to be respondents in this study. The data was collected using a questionnaire that was distributed via a link from the Google form. The data analysis technique used is descriptive analysis, the mean and grand mean. The results showed that the level of information literacy skills of Library Science students at UIN Sumatera Utara in preparing their thesis using the empowering model was high with an average score of 4.29 and was in the interval of 4.24 - 5.00.